The Effect of Acupuncture on Modulating Inflammatory Cytokines in Rodent Animal Models of Respiratory Disease: A Systematic Review and Meta-Analysis - Lee, Serin; Kim, Seung-Nam (Frontiers in Immunology, 2022)
Purpose: Although respiratory diseases (RD) are rapidly becoming a global health issue due to their high mortality and prevalence, there are limitations to the currently available treatments. Acupuncture has been recognized to mitigate many diseases by reducing inflammation and modulating cytokines. However, no systematic analysis has been performed to examine the effects of acupuncture on RD. We aimed to evaluate the effects of acupuncture on rodent animal models of RD. Methods: PubMed, EMBASE, MEDLINE, and the Research Information Service System were searched to retrieve studies that met our inclusion/exclusion criteria. The quality of each included study was evaluated using a 10-item checklist modified from the Collaborative Approach to Meta-Analysis and Review of Animal Data from Experimental Studies. With adequate data extracted, meta-analysis was performed using RevMan software. Results: A total of 18 studies were included, and the mean quality assessment was 5.7. The meta-analysis revealed that acupuncture had a significant effect on changing the cytokine levels, including pro-/anti-inflammatory, Th1-, Th2- and Th17- specific cytokines. Conclusion: Although there were limitations in the number of included studies, the results suggest that acupuncture can be a possible treatment for RD through its modulation of various cytokines, leading to reduced inflammation.